(untitled) (Medical Forum Monthly, 2024)
Objective: The primary goal of this study is to determine the diagnostic potential of PSA levels in prostate cancer, the histopathological pattern of aggression in terms of the Gleason grading system, and bone metastasis in a subset of the Karachi population. Study Design: Comparative cross-sectional study. Place and Duration of Study: This study was conducted at the Ziauddin University, Karachi on 126 prostate biopsy specimens from a subset of the Karachi population from February 2023 to January 2024. Methods: The samples were recruited after the histopathological confirmation and were composed of 68 prostate adenocarcinoma (PCA) and 58 benign prostatic hyperplasia (BPH) along with the clinic-pathological data. Quantitative analysis of PSA and Gleason scores was done. The area under the receiver operating characteristic curve (AuROC) was generated to determine the sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, negative likelihood ratio, and diagnostic accuracy of PSA level was evaluated for diagnostic performance with positive biopsy. One-way ANOVA was applied among different grades of PCA. Results: The PSA levels showed higher sensitivity (AuROC=0.999) for the diagnosis of PCA and good performance in determining tumoral grade and the possibility of distant metastasis. We found that PSA levels higher than 7.055 could be a threshold value for predicting PCA in suspected biopsy. Conclusion: The data showed that PSA can predict PCA, Gleason grade, and bone metastasis. In addition to that, we were able to document a threshold point to suspect PCA during the early pathological course.